Management and Complications of Dexamethasone Intravitreal Implant Migration Into the Anterior Chamber. (November 2022) - Betsch, Devin M.; Gupta, R. Rishi
Purpose: To report patient demographics, the clinical course, and visual outcomes across a case series of patients who experienced dexamethasone (DEX) intravitreal implant (Ozurdex, Allergan, Inc) migration into the anterior chamber (AC), with a focus on the corneal transplantation rate. Methods: In this retrospective cross-sectional study, a chart review of all cases was performed. For numerical responses, means and SDs were calculated. Percentages and absolute numbers were used to report the proportion of patients who experienced various outcomes of interest. Results: The study comprised 32 cases. All cases occurred in pseudophakic eyes; of those, 8 (25.0%) had posterior chamber intraocular lenses in the capsular bag with no known capsular or zonular issues. The mean duration from DEX implant injection to detection of migration was 19.4 ± 14.5 days. The DEX implant was explanted in 21 patients (65.6%) and repositioned in the vitreous cavity or subconjunctival space in 6 patients (18.8%). Twelve patients (37.5%) ultimately required corneal transplantation. Conclusions: To our knowledge, this is the largest case series of DEX intravitreal implant migration into the AC compiled to date. Cases of migration occurred in individuals with no known history of significant prior zonule disruption. This potential complication should be discussed with all patients undergoing DEX implant injection, which may aid in earlier presentation and improved visual outcomes.